2015
DOI: 10.1371/journal.pone.0121654
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids Extract, Hydrolyzed Collagen and Green Tea Extract Synergically Inhibit Inflammatory and Catabolic Mediator’s Synthesis by Normal Bovine and Osteoarthritic Human Chondrocytes in Monolayer

Abstract: The main objective of this study was to assess the in vitro effects of curcuminoids extract, hydrolyzed collagen and green tea extract in normal bovine chondrocytes and osteoarthritic human chondrocytes cultured in monolayer. This study also investigated the synergic or additive effects of these compounds. Enzymatically isolated primary bovine or human chondrocytes were cultured in monolayer until confluence and then incubated for 24 hours or 48 hours in the absence or in the presence of interleukin-1β and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 38 publications
3
36
0
2
Order By: Relevance
“… 58 , 59 , 67 , 68 Comblain et al demonstrated that curcuminoids decreased the gene expressions of MMP-3, ADAMTS4, ADAMTS5, COX-2, PGE-2, and IL-6. 56 They also found that the combination of curcuminoids, hydrolyzed collagen, and green tea extract were more effective in suppressing these genes than curcuminoids alone. 56 Currently, curcumin reduced the level of MMP-3 and aggrecans released into the media by the bovine chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 58 , 59 , 67 , 68 Comblain et al demonstrated that curcuminoids decreased the gene expressions of MMP-3, ADAMTS4, ADAMTS5, COX-2, PGE-2, and IL-6. 56 They also found that the combination of curcuminoids, hydrolyzed collagen, and green tea extract were more effective in suppressing these genes than curcuminoids alone. 56 Currently, curcumin reduced the level of MMP-3 and aggrecans released into the media by the bovine chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“… 56 They also found that the combination of curcuminoids, hydrolyzed collagen, and green tea extract were more effective in suppressing these genes than curcuminoids alone. 56 Currently, curcumin reduced the level of MMP-3 and aggrecans released into the media by the bovine chondrocytes. 56 This was in contrast with the findings of Mathy-Hartert et al, whereby production of aggrecans by chondrocytes was not affected by curcumin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphenol's benefits on health may be potentialized by other nutrients. For instance, the combination of curcuminoid extract, hydrolyzed collagen, and green tea extract was proven to be significantly more efficient in inhibiting interleukin-1 β-stimulated matrix metalloproteinase-3 expression than curcuminoid extract alone in normal bovine chondrocytes and osteoarthritic human chondrocytes cultures [31,32]. The same authors described a trended reduction of pain in an OA model when dogs were fed with the corresponding mixture for 3 months [33].…”
Section: Discussionmentioning
confidence: 99%